Liquefaction-Induced Large Ground Displacements: Part 2- Prediction by Energy Model - Orense, Rolando P. (Philippine Engineering Journal; Vol 15 No 2 (1994), 2021)
This paper deals with the modeling of liquefaction-induced large permanent ground displacements. Based on the information obtained from case studies and shaking table tests, a technique is developed to predict the ultimate ground displacements that will develop when the state of soil liquefaction is continued for a sufficiently long period of time. The method is based on principle of minimum potential energy, and the effect of earthquake motion is removed from the analysis. The distribution of the ground displacement is derived so that the potential energy of the ground would take minimum value. Surface irregularity as well as ground heterogeneity are considered. Both two-dimensional and three-dimensional models are developed. Finally, the model is extended to include the temporal development of permanent displacement. This is done by solving the equation of motion where the transient displacement is expressed as a fraction of the ultimate one. An energy dissipation mechanism is incorporated stabilize the solution. Analyses made on both laboratory and actual field cases show the validity of the model. Thus, the technique can serve as an economical and practical tool to predict the potential seismic hazards to urban facilities and lifeline networks induced by the lateral flow of liquefied soil.